Insights on the development of TCM nursing - Jun-Qiang Zhao; Fen Zhou; Ying Sun; Run-Xi Tian; Je Kan Adler-Collins; Yu-Fang Hao (Elsevier, 2016)
Background: Traditional Chinese medicine nursing (TCM nursing) is one of the highlights of nursing profession in China, which plays a significant role in Chinese healthcare system. However, bottlenecks exist in TCM nursing development. It's necessary to explore the discipline connotation and advantages of TCM nursing in nursing education and clinical practice and introduce modern nursing concepts. Methods: We analysis the connotations of TCM nursing, the bottlenecks it faces, and strategies to facilitate TCM nursing development. Results: Qualitative research method and evidence-based nursing concepts are key strategies to solve the dilemma TCM nursing confronts with and are quite essential in TCM nursing development. Conclusion: We should embed qualitative research method and evidence-based nursing concepts into TCM nursing advancement so as to facilitate the advancement of TCM nursing and promote its globalization.